Gaze-cueing effect depends on facial expression of emotion in 9- to 12-month-old infants - Niedźwiecka, Alicja; Tomalski, Przemysław (Frontiers in Psychology, 2015)
Efficient processing of gaze direction and facial expression of emotion is crucial for early social and emotional development. Towards the end of the first year of life infants begin to pay more attention to negative expressions, but it remains unclear to what extent emotion expression is processed jointly with gaze direction at this age. This study sought to establish the interactions of gaze direction and emotion expression in visual orienting in 9- to 12-month-olds. In particular, we tested whether these interactions can be explained by the negativity bias hypothesis and the shared signal hypothesis. We measured saccadic latencies in response to peripheral targets in a gaze-cueing paradigm with happy, angry, and fearful female faces. In the Pilot Experiment three gaze directions were used (direct, congruent with target location, incongruent with target location). In the Main Experiment we sought to replicate the results of the Pilot experiment using a simpler design without the direct gaze condition. In both experiments we found a robust gaze-cueing effect for happy faces, i.e. facilitation of orienting towards the target in the gaze-cued location, compared with the gaze-incongruent location. We found more rapid orienting to targets cued by happy relative to angry and fearful faces. We did not find any gaze-cueing effect for angry or fearful faces. These results are not consistent with the shared signal hypothesis. While our results show differential processing of positive and negative emotions, they do not support a general negativity bias. On the contrary, they indicate that towards the age of 12 months infants show a positivity bias in gaze-cueing tasks.